The Right of the Wife to Unknot the Marital Bond In the Algerian Family Law - Benaissi, Ahmed; Ben ferdia, Mohamed (Journal of Legal Studies and Researches, 2023)
This article aims to shed light on the wife’s right to break the marital bond through divorce and khul’. The Algerian legislator strengthened this right after amending the Family Code by virtue of Ordinance 05-02, expanding the cases of divorce, and raising the khul’ from the license to the original right. This is in order to achieve a balance between the positions of men and women in the termination of the marriage contract.